Arabic Learning Strategies Through Tiktok Entertainment Content to Attract Interest in Learning Arabic - Dinia, Hima Roiku; Jannah, Mawaddatul; Mustofa, Syaiful; Helalsah, Ibrahim (UIN ANTASARI, 2024)
TikTok content is increasingly in demand by young people in Indonesia. Based on We Are Social data, Indonesia was recorded as the country with the second largest TikTok users in the world in January 2024, namely 109.90 million users with the majority being school-age children. Thus, this platform has the potential to be utilized as an innovative and modern medium for learning Arabic. This study aims to explore strategies for learning Arabic through TikTok in attracting interest in the language using descriptive qualitative observation techniques. The researcher conducted an in-depth analysis of the learning content and the audience's response through the comments column. The results of this research indicate that strategies for learning Arabic through TikTok that collaborate with the latest trends followed by young people can attract students' interest in learning. The recommendation is that learning Arabic through TikTok engages audiences and provides a dynamic and modern learning environment.